2016
DOI: 10.1039/c6cy01763k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon supports on RhRe bifunctional catalysts for selective hydrogenolysis of tetrahydropyran-2-methanol

Abstract: Orders-of-magnitude differences in hydrogenolysis activity were observed between RhRe/C catalysts with different carbon supports, which is due to the types of bimetallic particles that are formed on the different carbon supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…These are attributed to B−O−H deformations, [49,51–54] B−O stretching of BO 3 units, [53–55] and C=C stretching from the support, respectively [47] . On non‐borated OAC, the features at 1756 and 1580 cm −1 are assigned to C=O and conjugated aromatic C=C functional groups, respectively [47,56] . It is important to note that C=O peak at 1756 cm −1 is absent in B/OAC (fresh and spent), suggesting a high fraction of C=O sites on the surface of the carbon support are consumed by boron during impregnation of H 3 BO 3 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are attributed to B−O−H deformations, [49,51–54] B−O stretching of BO 3 units, [53–55] and C=C stretching from the support, respectively [47] . On non‐borated OAC, the features at 1756 and 1580 cm −1 are assigned to C=O and conjugated aromatic C=C functional groups, respectively [47,56] . It is important to note that C=O peak at 1756 cm −1 is absent in B/OAC (fresh and spent), suggesting a high fraction of C=O sites on the surface of the carbon support are consumed by boron during impregnation of H 3 BO 3 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Deconvolution of the broad OAC peak at 1240 cm −1 results in 3 species at 1115, 1238, and 1398 cm −1 (Figure 4b). These are attributed to oxygen functionalities of either C−O‐C, [56] O−H bending or C−O stretching, [47] and carboxylic acid −O−H bending [57] . Much of this broad peak appears to be consumed following boron impregnation as evidenced by the absence of such a peak in the fresh and spent B/OAC spectra, corroborating the observation that boron consumes C=O/C−O species on the surface of the carbon support.…”
Section: Resultsmentioning
confidence: 99%
“…17 Karanjkar et al reported an enhanced hydrogenolysis of cyclic ethers, such as tetrahydropyran-2-methanol, over a ReO x -promoted Rh/C catalyst. 18 Regarding phenol derivatives, Lamb et al reported Pd-Re bimetallic synergy for the HDO of guaiacol to cyclohexane. 19 The enhanced HDO activity of these bimetallic catalysts is generally understood to follow a bifunctional mechanism, in which the noble metals, such as Pd and Rh, provide the hydrogenation function, and Re (or ReO x ) promotes the deoxygenation activity.…”
mentioning
confidence: 99%
“…The electrocatalysts without Nb displayed a higher contact angle (Figure ), indicating higher hydrophobicity than electrocatalysts containing Nb. The hydrophilicity of an electrocatalyst plays an important role in heterogeneous catalysis, due to the bifunctional effect of weakly H 2 O adsorption and dissociating to OH − +H + ions . Thus, Nb addition to the electrocatalysts favors the bifunctional mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophilicity of an electrocatalyst plays an important role in heterogeneous catalysis, due to the bifunctional effect of weakly H 2 O adsorption and dissociating to OH À + H + ions. [14,32] Thus, Nb addition to the electrocatalysts favors the bifunctional mechanism.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%